Evaluation and characterization of Pleurotus eryngii extract-loaded chitosan nanoparticles as antimicrobial agents against some human pathogens - Acay, Hilal; Yildirim, Ayfer; Guzel, Elif Erdem; Kaya, Nalan; Baran, Mehmet Firat (Taylor & Francis Inc, 2020)
With the increase of antibiotic resistance, which is present at a worrying rate, research on the use of newly developed nanoparticles as an antimicrobial agent with green biotechnology has intensified. The study aimed to investigate the antimicrobial effects of chitosan nanoparticles (CSNP) synthesized using Pleurotus eryngii extract (PE). Characterization of P. eryngii-loaded chitosan nanoparticles (PE-CSNPs) was performed with Fourier transform infrared spectrophotometer, X-ray diffraction, Field-emission scanning electron microscopy, Brunauer-Emmett-Teller, Differential scanning calorimetry, and zeta potential techniques. The FE-SEM images showed that the surface morphology of nanoparticles is similar to CS, but has more porosity network and smaller dimensions structure. The average particle size of spherical PE-CSNPs was obtained as 330.1 nm. The specific surface area and average pore diameter of the synthesized nanoparticles were found as 3.99 m(2)g(-1) and 2.25 nm, respectively. X-ray diffraction determines the presence of an amorphous peak at 2 theta = 21.2 degrees results from CS and PE. PE-CSNPs synthesized using P. eryngii extract showed strong antimicrobial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Candida albicans as 0.0156, 0.0625, 0.0625 and 0.0312 mg ml(-1), respectively. Thus, it was determined that chitosan nanoparticles formed by the green synthesis of P. eryngii extract showed strong anti-microbial properties.
Keywords: Antimicrobial effects; chitosan; DSC; Pleurotus eryngii; zeta potential